FORMATION OF PROFESSIONAL SELF-DETERMINATION OF TEACHERS ON THE BASIS OF ACTIVATION OF CREATIVE INDEPENDENCE - Bekoeva, M.I (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article is devoted to the justification of activities to enhance the creative independence of students as a condition for the success of their professional self-determination based on the exchange of semantic, individual inclinations, ways of activity and personal self-development and self-regulation. The author proves the need to link the content of education with future professional activities. Thus, such content increases the interest in research, while establishing a correspondence between the content and future professional activity. In the formation of professional self-determination of the future employee in the learning process, it is necessary to activate creative autonomy, which determines the nature of the personal orientation in the field of future professional activity. In this case, training should be contextual, student-centered, professional-oriented. The contextual content assumes the content of training, which is characterized by the rejection of the formalized transfer of ready-made knowledge and social norms, enriched by a creative approach, and various competencies reflecting interdisciplinary integration processes, professional orientation, priorities of higher education and the requirements of the modern labor market to the specialist model of the new profile. The article convincingly proves the fact that for the successful formation of professional self-determination based on enhancing the creative independence of students, introducing innovative technologies into the educational space of a modern educational organization, the teacher's position as a leader should not be authoritarian, but always democratic, and the teaching and educational process should be carried out on a subject-subject interaction basis. Education should provide the student with more freedom to exercise their independence, cognitive activity, connecting its content with the interests, aspirations and needs of students.